Optimalisasi Penataan Ruang Melalui Sosialisasi Kebijakan dan Peraturan Perundang-Undangan di Kabupaten Majalengka - Iwan Satibi; Yaya Mulyana; Ediyanto; Yayan Andri (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
Abstract: Community service is an effort to improve the quality of human resources. including broadening horizons, knowledge, and in order to improve skills carried out by academics as proof of dharma filial piety and implementation of forms of caring to play an active role in improving the quality of human resources and increasing welfare. Postgraduate Postgraduate Public Policy and Administration Masters Program at Pasundan University carries out Optimization of Spatial Planning through Socialization of Legislation in Majalengka Regency. Participantsin the Socialization of Policies and Legislation in the Spatial Planning Sector in Majalengka Regency are all stakeholderssuch as: government agencies, institutions, community leaders, and entrepreneurs. The socialization activities yielded results, namely the socialization of a number of regulations and policies related to spatial planning, business permits, space utilization and so on. Socialization of Spatial Planning Policies and Legislation in Majalengka Regency was carried out well as a whole by the Regional Government. Of course, in this case it is necessary to coordinate between related agencies so that problems regarding spatial planning and investment activities can be synchronized. The socialization provided to all stakeholders can increase knowledge about spatial planning, foster community understanding and responsibility in implementing spatial planning and more importantly all stakeholders can participate in carrying out development in accordance with spatial planning objectives. After carrying out this socialization, all relevant stakeholders can understand the implementation of risk based business licenses in relation to the Spatial Planning policy in Majalengka Regency.